The Effect of Application of Crossword Puzzle Learning Strategy on Student Learning Outcomes - Enirudh Bheke; Slegh Pritem; Subhasih Pujarih (Newinera Publisher, 2021)
The function of the crossword puzzle itself is to develop brain nerves that have a refreshing effect on memory, allowing the brain's work function to return to its optimal state because the brain has become accustomed to continuously learning in a relaxed manner. The design of this study is a pre-experimental research design of the type One-Group Pretest-Posttest Design, which is used in pre-experimental research. Because the outcomes of the therapy may be compared to the circumstances before to treatment, the results of the treatment can be known with more accuracy in this research (treatment). The percentages of student learning objectives that were acquired are: low at 6.67%, moderate at 16.67%, high at 40%, and very high at 16.67%. Based on the data gathered, it can be stated that, on the whole, adopting the Crossword Puzzle learning method has a notable effect on students' learning outcomes, as 36.67% of students achieved this level, and 46.67% of students attained this level